Genome Assembly and Transcriptome Analysis of the Fungus Coniella diplodiella During Infection on Grapevine (Vitis vinifera L.) - Liu, Ruitao; Wang, Yiming; Li, Peng; Sun, Lei; Jiang, Jianfu; Fan, Xiucai; Liu, Chonghuai; Zhang, Ying (Frontiers in Microbiology, 2021)
Grape white rot caused by Coniella diplodiella (Speg.) affects the production and quality of grapevine in China and other grapevine-growing countries. Despite the importance of C. diplodiella as a serious disease agent in grape was reported, the genome information and molecular mechanisms underlying its pathogenicity are poorly understood. To bridge these gaps, the genome of C. diplodiella strain WR01 which consists of 40.93 Mbp was de novo assembled. A total of 9403 putative protein-coding genes were predicted. Among those, 608 and 246 genes are potential secreted proteins and candidate effector proteins (CEPs), respectively. Additionally, transcriptome of C. diplodiella was analyzed after feeding with crude grapevine leaf homogenates, which reveals the transcriptional expression of 9115 genes. Gene ontology enrichment analysis indicated that the highly enriched genes are related with carbohydrate metabolism, secondary metabolite synthesis. Forty-three putative effectors were cloned from C. diplodiella, and applied for further functional analysis. Among them, two proteins exhibit strong effect in suppression of BCL2-associated X (BAX)-induced hypersensitive response after transiently expressed in Nicotiana benthamiana leaves. This work facilitates valuable genetic basis for understanding the molecular mechanism underlying C. diplodiella-grapevine interaction.